(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To determine the prevalence and severity of depression among caregivers of hospitalized patients at the medical and pharmaceutical university hospital in 2026. Methods: A cross-sectional descriptive study was conducted on 330 caregivers of inpatients at the medical and pharmaceutical university hospital from January 2026 to April 2026. Results: The proportion of caregivers with depressive symptoms was 51.2%, among them, the risk of depression accounted for 22.7%; 9.7% mild depression, 9.7% moderate, and 9.1% severe depression. The mean depression score was 7.5 ± 7.2, indicating a level at risk of depression. Conclusion: Depression among caregivers of hospitalized patients was relatively common, with nearly half being at risk of or experiencing depressive symptoms. These findings highlight the need to strengthen screening, psychological counseling, and appropriate support measures to reduce caregiver burden and improve caregivers’ quality of life.